Acquired Carotid-Jugular Fistula: Its Changing History and Management. (8th July 2013) - Caldarelli, Claudio; Biricotti, Marco; Materazzi, Gabriele; Spinelli, Claudio; Spisni, Roberto
Abstract : Purpose . To highlight the changes that have come about in recent years in the etiology, diagnosis, and treatment of acquired carotid-jugular fistulas. Methods . We present a review of the literature on acquired carotid-jugular fistulas (CJFs), which includes studies from World Wars I and II up to today and a retrospective analysis of the lesion reports published in the period 2000–2012, with an update of Talwar's table. The case study of one patient suffering from an untreated, long-standing CJF recently treated by us is also presented and included in the updated table. Results . Thanks to early treatment of acute lesions by reconstructive and endovascular surgery, incidence of posttraumatic carotid-jugular fistulas is decreasing, while the number of iatrogenic ones due to medical advances is concomitantly increasing, specifically because of the ever more widespread use of central venous catheters for venous pressure monitoring, parenteral nutrition, and hemodialysis. Conclusion . Although such lesions seem destined to diminish in the future thanks to the above-mentioned diagnostic and therapeutic advances, the increasing number of internal jugular vein catheterizations performed worldwide implies that physicians will still be dealing with carotid-jugular fistulas for many years to come.